Frontiers of faith : the Christian encounter with Manichaeism in the Acts of Archelaus - BeDuhn, Jason.; Mirecki, Paul Allan. (Nag Hammadi and Manichaean Studies, 2007)
Taking as their common subject the key early Christian anti-Manichaean work, the Acts of Archelaus ( Acta Archelai ), the contributors to this volume offer a systematic exploration of what the text has to tell us about inter-religious contact, conflict, and comprehension at a crucial moment in religious history: the encounter between Christianity and Manichaeism along the political and cultural frontier zone of West Asia in the early fourth century CE. The contributions examine the text's structure, apologetic and polemical strategies, and possible sources, and through these analyses challenge received notions of 'orthodoxy' and 'heresy' in the mutual construction of identity that took place between these two claimants to the Christian heritage.